PELATIHAN AKUNTANSI BERBASIS KOMPUTER MENGGUNAKAN PROGRAM ACURATE DALAM UPAYA MENINGKATKAN KOMPETENSI SISWA SMK JURUSAN AKUNTANSI DI KOTA PONTIANAK DALAM MEMASUKI PASAR TENAGA KERJA DI ERA REVOLUSI INDUSTRI 4.0. - kartikawati, Theresia siwi; Kurniasih, Ninik; Yuliana, Elsa Sari; Zawitri, Sari; Al Farizi, Zulham; Soraya; Ariyanto; Wahyudi; Rahmaniar, Risti (Sehati Abdimas, 2023)
The rapid development of science and technology is currently bringing big leaps in almost all aspects of life, which has resulted in many activities becoming digitally based. The industrial sector is the sector that is quickest to adopt this technological development, conventional industrial activities are developing towards industrial digitalization. Likewise, in bookkeeping and preparing financial reports, most industries have implemented technological advances in data processing, so that it is no longer done manually. Several software have been developed to support digitization in bookkeeping and preparation of company financial reports, including the Accurate accounting computer program. This development must be immediately responded to by educational institutions such as Vocational High Schools (SMK) which produce graduates in the field of accounting, to equip their students with practical mastery. computerized accounting. So that the graduates produced are competitive in the labor market and have high competence to be able to work together with technological developments that have been implemented in industry. However, not all educational institutions have computer laboratories that are equipped with accounting software, so students cannot carry out computerized accounting practices. Keywords: Accounting Practices, Competence, Accurate Application.